2018
DOI: 10.18843/ijms/v5i2(6)/13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Resource Development (HRD) Practices on Organizational Effectiveness: The Role of Employee Competencies

Abstract: The aim of this paper is to examine the influence of HRD practices on organizational effectiveness by means of employee competencies. An integrated research model was developed by combining principal factors from existing literature. Data were collected through questionnaire from 600 employees of the selected SME's. The validity of the model and hypotheses were tested using structural equation modeling (SEM). The reliability and validity of the dimensions are established through confirmatory factor analysis (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Research studies suggest that competence plays a significant role in improving the performance of employees, which subsequently results in the achievement of organizational goals. Potnuru and Sahoo (2016) and Otoo and Mishra (2018a, 2018b) argue that there exists a significant and positive relationship between human resource development practices and employee competence, which in turn determines the success of an organization in contemporary businesses. Therefore, using a competence approach in executing the functions of human resource development, organizations would be able to gain sustainable competitive advantage resulting from well-developed and robust competence in the base and superior performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies suggest that competence plays a significant role in improving the performance of employees, which subsequently results in the achievement of organizational goals. Potnuru and Sahoo (2016) and Otoo and Mishra (2018a, 2018b) argue that there exists a significant and positive relationship between human resource development practices and employee competence, which in turn determines the success of an organization in contemporary businesses. Therefore, using a competence approach in executing the functions of human resource development, organizations would be able to gain sustainable competitive advantage resulting from well-developed and robust competence in the base and superior performance.…”
Section: Introductionmentioning
confidence: 99%
“…Personal development is highlighted in most of the literature studies. There are major personality development roles for employee motivation and loyalty including performance appraisal, 360degree feedback, and consistent meetings for the employee performance analysis (Otoo and Mishra, 2018). The training can be based upon the analysis, the training measures, the skills required for the job criteria, and its long-run assessment time for the employee motivation.…”
Section: Personal Developmentmentioning
confidence: 99%
“…The author found that creative climate plays a mediating role between HRM practices and organisational performance. Further, a number of researchers have found that HRD practices influence organisational performance and, in particular, employee competencies plays a mediating role between the two constructs (Otoo and Mishra, 2018). In a similar study, Otoo et al (2019) found that employee performance mediates the relationship between HRD practices and organisational performance.…”
Section: Literature Reviewmentioning
confidence: 99%